Espresso Coffee Consumption and Risk of Coronary Heart Disease in a Large Italian Cohort - Grioni, Sara; Agnoli, Claudia; Sieri, Sabina; Pala, Valeria; Ricceri, Fulvio; Masala, Giovanna; Saieva, Calogero; Panico, Salvatore; Mattiello, Amalia; Chiodini, Paolo; Tumino, Rosario; Frasca, Graziella; et al. (PloS one, 2015)
The relationship between coffee consumption and coronary heart disease (CHD) has been investigated in several studies with discrepant results. We examined the association between Italian-style (espresso and mocha) coffee consumption and CHD risk. We investigated 12,800 men and 30,449 women without history of cardiovascular disease recruited to the EPICOR prospective cohort study. Coffee consumption was assessed at baseline. In a random sub-cohort of 1472 subjects, plasma triglycerides, and total, LDL and HDL cholesterol were determined to investigate the effect of coffee consumption on plasma lipids. After a mean follow up of 10.9 years, 804 cases of CHD (500 acute events, 56 fatal events and 248 revascularizations, all first events) were identified. Multivariable adjusted hazard ratios for CHD were: 1.18 (95% CI 0.87-1.60) for drinking 1-2 cups/day, 1.37 (95% CI 1.03-1.82) for >2-4 cups/day and 1.52 (95% CI 1.11-2.07) for over 4 cups/day (P trend <0.001) compared to reference (<1 cup/day). Plasma triglycerides, and total, LDL and HDL cholesterol did not vary significantly (ANOVA) with coffee consumption. Consumption of over 2 cups/day of Italian-style coffee is associated with increased CHD risk, but coffee consumption was not associated with plasma lipid changes, so the adverse effect of consumption appears unrelated to lipid profile.